2005
DOI: 10.1590/s1519-69842005000100002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal changes in the diet of Oligosarcus hepsetus (Characiformes, Characidae) in a Brazilian Reservoir

Abstract: We assessed spatial and seasonal changes in the diet of Oligosarcus hepsetus in order to describe the strategy developed by this species that allows their very high abundance in Lajes reservoir, Rio de Janeiro, Brazil. Fish samplings were carried out using gill nets, deployed during ca. 12 and 24 hours, between April 2001 and May 2002. A total of 289 individuals were examined, of which 97 showed gut contents. We used the index of relative importance (IRI) to compare probable dietary shifts, and the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 2 publications
2
25
1
2
Order By: Relevance
“…The Alimentary Preference Degree for the items consumed by Oligosarcus hepsetus showed that the items were occasional, and when these were grouped, the first three items were secondary: Insects (nymphs and pupas); Insects (adults) and Fish. This result was confirmed by Araújo et al (2005) in Lajes Reservoir, where Oligosarcus hepsetus showed a carnivorous feeding habit, feeding only on insects and fish and varying its diet according to the seasons and the zones of the reservoir.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The Alimentary Preference Degree for the items consumed by Oligosarcus hepsetus showed that the items were occasional, and when these were grouped, the first three items were secondary: Insects (nymphs and pupas); Insects (adults) and Fish. This result was confirmed by Araújo et al (2005) in Lajes Reservoir, where Oligosarcus hepsetus showed a carnivorous feeding habit, feeding only on insects and fish and varying its diet according to the seasons and the zones of the reservoir.…”
Section: Discussionmentioning
confidence: 52%
“…Hahn et al (2000) found only fish in the stomachs of individuals of Acestrorhyncus lacustris over 10 cm long in the Itaipu Reservoir. Araújo et al (2005) observed a similar situation, in which Oligosarcus hepsetus larger than 19 cm fed principally on fish, in contrast to smaller individuals which fed principally on insects. Similarly, Gealh and Hahn (1998) found for Oligosarcus longirostris in the Segredo Reservoir, that smaller individuals fed on insects, crustaceans and fish, whereas larger ones (>16 cm) were exclusively piscivorous.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Oligosarcus has also been recorded in reservoirs (Castro 1996, Gealh & Hahn 1998, Araújo et al 2005, Luz-Agostinho et al 2006, Terra & Araújo 2011, and, in the specific case of O. paranensis, ichthyofaunal suveys have reported its occurrence in the Atibainha, Cachoeira, Taiaçupeba and Itupararanga Reservoirs in the State of São Paulo (Castro & Arcifa 1987, Smith & Petrere Junior 2008 and at Fiú, Mourão, Capivari and Rio dos Patos Reservoirs in the State of Paraná (Luiz et al 2003). The abundance of this species varied among those ecosystems; however, at Fiú and Mourão, O. paranensis stood out during captures (the most and the second most abundant species, respectively).…”
Section: Introductionmentioning
confidence: 98%